SUPPRESSION OF SUBSYNCHRONOUS RESONANCE WITH THE AID OF AN AUXILIARY EXCITATION CONTROL SIGNAL. - Limebeer, D; Hartley, R; Lahoud, M (1983)
Results are presented of an investigation into the possible suppression of subsynchronous resonance (SSR) instability of the 1072 MVA nuclear powered turbo-generators to be installed at Koeberg Power Station in South Africa. The auxiliary excitation control strategy considered feeds a signal derived from generator speed through a phase advance compensator into the rotary excitation system. It is found that the classical automatic voltage regulator and governor loops are of little use in suppressing subsynchronous resonance, and that the auxiliary excitation control signal is only of limited use. The two main limiting factors are the slow speed of response of the existing conventional exciter and its inadequate ceiling voltage levels.